Enhancing competitiveness in India’s electric vehicle industry: impact of advanced manufacturing technologies and workforce development - Silambarasan Rajendran; Chander Prakash; Mustafa Shakir; Mamdooh Alwetaishi; Ratchagaraja Dhairiyasamy; Parvathy Rajendran; It Ee Lee (Scientific Reports)
Abstract The primary objective of this study is to explore how advanced manufacturing technologies and workforce development can enhance the competitiveness of India’s electric vehicle (EV) industry. The study combines data collection, statistical analysis, and expert interviews using a mixed-methods approach. Quantitative data on production efficiency, quality control, and workforce skills were analyzed using ANOVA and regression, while qualitative insights provided contextual understanding. Results indicate that adopting advanced technologies such as automation, robotics, and Industry 4.0 solutions significantly improves production efficiency and product quality. A leading Indian EV manufacturer reported a 30% reduction in production time and a 25% increase in product quality after integrating robotic assembly lines. Workforce development programs, like the collaboration between Ashok Leyland and IIT Madras, substantially improved worker competencies, addressing the skill gap in advanced manufacturing systems. Comparative analysis revealed India’s EV manufacturing metrics lag behind global leaders, emphasizing the need for increased investments in manufacturing infrastructure and targeted training programs. The study concludes that strategic investments in advanced technologies and workforce development are essential for reducing import dependency, streamlining manufacturing processes, positioning India as a competitive player in the global EV market, and offering actionable recommendations for policymakers and industry stakeholders.